Sonographic evaluation of enthesopathy in rheumatoid arthritis patients - Samar Tharwat; Mohammed Kamal Nassar; Asmaa Enein; Muhammad Emran Asad (SpringerOpen, 2019)
Background Rheumatoid arthritis (RA) is one of the most common autoimmune diseases. It affects mainly the synovial membranes of the small joints. However, it may also have extra-articular manifestations. Enthesopathy may occur as one of the extra-articular manifestations of RA and is not clinically detected. Ultrasound (US) is a relatively new tool for the detection of enthesopathy. Aim The aim of this study was to assess the presence and distribution of enthesopathy in RA patients using US. Patients and methods Twenty-nine consecutive patients with RA and 14 age-matched healthy controls were included in this study. All RA patients met the 2010 American College of Rheumatology/European League Against Rheumatism classification criteria for RA. Six entheses sites were evaluated using gray scale and Doppler US with a linear transducer and were scored using the Madrid Sonography Enthesitis Index (MASEI). Results US detected the presence of enthesopathy in patients with RA. There was a statistically significant difference in the enthesopathy score of plantar aponeurosis insertion and Achilles tendon insertion. The total enthesopathy score was statistically significant in patients with RA versus controls. Conclusion US entheseal abnormalities are present in a high percentage of RA patients. US enthesopathy is not associated with disease activity in RA patients.